The Alliance on Business Education and Scholarship for Tomorrow a 21st century organization (ABEST21) Peer Review Team (PRT) visit - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2024)
The ABEST21 Peer Review Team (PRT) visit to Arshad Ayub Graduate Business School (AAGBS) provided an important platform for evaluating AAGBS's academic quality, governance, teaching and learning practices, and overall institutional performance in line with international accreditation standards. The ABEST21 delegation was led by Prof. Dr. Fumio Itoh (President and CEO, ABEST21 International) and included Prof. Dr. Zulkornain Yusop (ABEST21 International Accreditation Advisor and Former President and CEO, Putra Business School, Malaysia), Yuka Nakagawa (ABEST21 Accreditation Manager), Assist. Prof. Dr. Hen Kai Wah (International College, Tunghai University, Taiwan), Assoc. Prof. Arief Wibisono Lubis, Ph.D (Faculty of Economics and Business, Universitas Indonesia, Indonesia), and Assoc. Prof. Caroline Tan, Ph.D (University of Tsukuba, Japan).